A Novel Case of Biliary Atresia in a Premature Neonate With 1p36 Deletion Syndrome - Vonita Chawla MD; Miran Rhee Anagnost MD; Alaa-Eldin Eldemerdash MD; Dahna Reyes MD; Rebecca Scherr MD; Kanayo Ezeanolue MD; Francis Banfro MD; Rabea Alhosh MD (SAGE Publishing, 2018)
We describe the case of a premature male neonate diagnosed with biliary atresia who was found to have chromosome 1p36 deletion syndrome. Our patient was born prematurely, at a gestational age of 28 weeks. Pregnancy was complicated by advanced maternal age, gestational hypertension, and intrauterine growth restriction. Physical examination revealed several dysmorphic features, prompting a genetic evaluation, which revealed chromosome 1p36 deletion syndrome. At week 7 of life, he was found to have acholic stools. Direct bilirubin was found to be elevated despite discontinuation of total parenteral nutrition at 3 weeks of life, thus raising the suspicion for biliary atresia. Biliary atresia was confirmed by constellation of clinical, imaging and intraoperative findings. First reported in 1996, 1p36 deletion syndrome has been researched increasingly and several new phenotypic associations have been reported over the years. While attempts at linking specific phenotypic abnormalities with individual gene(s) deletion(s) are being made, deletion patterns that would affect specific organ system or function remain to be fully understood. Thus, clinicians currently rely on reports of previously identified abnormalities. To our knowledge, our patient is the first report of biliary atresia in a patient with chromosome 1p36 deletion syndrome. It is important to determine the etiology of the cholestasis, when present, while caring for premature neonates with 1p36 deletion syndrome. This is necessary to avoid assuming that the cholestasis is arising from total parenteral nutrition administration and not from other gastrointestinal anomalies including biliary atresia, which is a time-sensitive diagnosis.